Le jeu des registres langagiers comme une stratégie du jeu avec le lecteur dans les romans de Raymond Queneau - Maziarczyk, Anna (Verbum – Analecta Neolatina, 2006)
Queneau's language has been analysed many times, mostly from a linguistic point of view, with special attention being paid to such procedures as phonetic transcription, lexical and syntactic mistakes or vocabulary typical of colloquial speech. However, Queneau's aim is not simply to imitate spoken discourse. Underlining of the oral aspect of a literary text emphasises its ludic character, i.e., its being - in a sense - the author's intellectual game with the reader. Queneau's linguistic experiments are not just limited to the most frequently mentioned techniques, by means of which he introduces the spoken discourse into literature. Simultaneously, Queneau employs very sophisticated, precise or even technical vocabulary as well as varied stylistic figures, often very complex. The present article analyses this play of linguistic registers, which constitutes the originality of Queneau s style and demonstrates that it is the conscious strategy of the author, who, rejecting established linguistic norms and literary conventions, plays with the reader.